Dermatomyositis: analysis of 109 patients surveyed at the Hospital das Clínicas (HCFMUSP), São Paulo, Brazil - Luciena Cegatto Martins Ortigosa; Vitor Manuel Silva dos Reis (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: Dermatomyositis affects striated muscles, skin and other organs. OBJECTIVE: To characterize the disease from January 1992 to December 2002, assessing its classification, cutaneous and systemic manifestations, and also laboratory results, therapeutic and prognostic findings compared to those in the literature. METHODS: Data were obtained from medical records of 109 patients who were classified into five groups: 23 juvenile dermatomyositis; 59 primary idiopathic dermatomyositis; 6 amyopathic dermatomyositis; 7 dermatomyositis associated with neoplasms and 14 dermatomyositis associated with other connective tissue diseases. RESULTS: Sixty patients were classified as "definite" diagnosis; 33 as "possible"; four as "probable" and 12 and as amyopathic. The average age at diagnosis was 36 years. Cutaneous manifestations occurred in all patients; the most frequent symptom was loss of proximal muscle strength; the most common pulmonary disorder was interstitial lung disease, and gastritis was the most prevalent digestive manifestation. Tumors were documented in 6.42% of cases. Lactate dehydrogenase was the muscle enzyme most frequently elevated in the majority of cases. Skin biopsies were performed in 68 patients; muscle biopsies in 53; and electroneuromyographies in 58 patients. The most commonly used treatment was corticotherapy and the mortality rate was 14.7%. CONCLUSION: in this sample, the disease appeared in younger individuals, was more frequent in women and the association with cancer was small.